Perception and Practices of Menstrual Taboos among Adolescent Girls in Urban Setting of Lalitpur: A Mixed-Method Study - Karki, Dikshya; Subedi, Madhusudan (Tribhuvan University Journal, 2025)
Menstruation, a natural phenomenon experienced by more than half the world’s population, is profoundly shaped by social norms, cultural beliefs and gendered practices. In Nepal, menstruation equates to ritual impurity. Although menstrual rituals are present throughout the country in many forms, academic research on the issue has mostly focused on the Chhaupadi Pratha. This research aimed to identify the menstrual taboos prevalent among adolescent girls in a metropolitan area and trace the reasons for their existence. A mixed-method study was conducted in one private and one public school in Lalitpur. A survey was used to gather the quantitative data among 400 students which was analyzed using IBM SPSS 20. One focus group discussion was then held in each school to collect the qualitative insights. Thematic analysis was applied and the responses are presented verbatim. Results revealed that 75.3% of the participants practice menstrual restrictions every month. The longevity of such customs is rooted in the masking of patriarchal expectations as cultural norms, the narrative of menstruation as an issue that only concerns heterosexual women, generational reinforcement of menstrual stigma, lack of women’s agency and women’s self-objectification. Although reproductive health education plays an important role in changing perceptions, the elimination of menstrual taboos requires multi-level interventions that begin at home.